Germination of mcm microconidia of Neurospora crassa - Alka Pandit (Fungal Genetics Reports, 1993)
Uninucleate microconidia of high germinability are desirable for measurement of nuclear ratios, recovery of homokaryons following transformation by DNA and for isolation of mutants. The mcm genotype of Neurospora crassa (RM 39-8A; FGSC 7091, a sixth generation progeny from a cross of 74-ORS-6a x Vickraman A) produces abundant microconidia by microcycle microconidiogenesis in liquid shake cultures at 22oC (Maheshwari 1991 Exp. Mycol. 15:346-350).